A critical role for IRF5 in regulating allergic airway inflammation - Byrne,AJ; Weiss,M; Mathie,SA; Walker,S; Eames,HL; Saliba,D; Udalova,IA; Lloyd,CM (Mucosal Immunology, 2016)
Interferon regulatory factor 5 (IRF5) is a key transcription factor involved in the control of theexpression of pro-inflammatory cytokine and responses to infection, however its role in regulatingpulmonary immune responses to allergen is unknown. We used genetic ablation, adenoviralvector-driven overexpression and adoptive transfer approaches to interrogate the role of IRF5 inpulmonary immunity and during challenge with the aero-allergen, house dust mite. Global IRF5deficiency resulted in impaired lung function and extracellular matrix (ECM) deposition. IRF5was also essential for effective responses to inhaled allergen, controlling airway hyper-responsiveness, mucus secretion and eosinophilic inflammation. Adoptive transfer of IRF5-deficient alveolar macrophages into the WT pulmonary milieu was sufficient to drive airwayhyper-reactivity, at baseline or following antigen challenge. These data identify IRF5-expressingmacrophages as a key component of the immune defence of the airways. Manipulation of IRF5activity in the lung could therefore be a viable strategy for the redirection of pulmonary immuneresponses and thus, the treatment of lung disorders.